Nucleated Red Blood Cell in Cord Blood as a Marker of Perinatal Asphyxia - Kanodia, Piush; Bhatta, Nisha Keshary; Singh, Rupa Rajbhandari; Shah, Gauri Shankar; Yadav, Shankar Prasad; Yadav, Sunil Kumar (Journal of Nepal Paediatric Society, 2016)
Introduction: Perinatal asphyxia is a common problem with the incidence varying from 0.5 –2% of live births. According to World Health Organization, approximately 4 million babies die each year before they reach the age of one month. The number of NRBC/100 WBC is variable but is rarely greater than 10 in normal neonates. This simple test can be helpful in the rapid assessment of perinatal asphyxia. Material and Methods: This prospective case-control study and there were 82 newborns in Case and 82 newborns in Controls comprising of asphyxiated and nonasphyxiated neonates, respectively, over a period of 12 months. Results: Out of the 82 neonates in case group, fifty nine (59) neonates were found to have NRBC level ≥10/100WBC, out of which 58 (70.7%) were cases and 1(1.2%) was a control. NRBCs count of ≥10/100WBC were seen more in the newborn who had low 5 min Apgar score and in the newborn with severe HIE, these association were statistically significant (P value <0.001). The cut-off NRBC value of ≥10/100WBC also found to have a sensitivity of 70.30% with a specificity of 98.78%. NRBC has a positive predictive value of 98.31% with a negative predictive value of 77.14%. Significance and sensitive area for ROC curve was 0.875. The ROC curve was calculated with cut-off NRBC value of ≥10/100WBC. Conclusions: NRBC counts can be very useful to differentiate HIE newborns from non-HIE newborns which will help in appropriate management and better outcome of these newborns. J Nepal Paediatr Soc 2015;35(3):264-268